Adaptation of Imla’ Learning Based on the KMI Curriculum at Darul Faizin Islamic Boarding School Caringin Bogor: English - Nadia Syekar Kamila; Fachrur Razi Amir; Agus Mulyana (Tatsqifiy: Jurnal Pendidikan Bahasa Arab, 2026)
The purpose of this study is to evaluate imla’ learning at SMP Darul Faizin Caringin Bogor, based on the Kulliyatul Mu’allimin Al-Islamiyah (KMI) curriculum, specifically considering students with diverse levels of Arabic language proficiency. To conduct this research, a descriptive qualitative approach was used; classroom observation, interviews with teachers and students, and analysis of learning documents were all part of this approach. The research findings indicate that imla’ learning is based on the pesantren’s internal curriculum, with the book Qawā’id al-Imlā’ as the primary source. To accommodate students’ varying abilities, the imla’ al-masmū’ method as the core method is combined with variations of manqūl, mandzūr, and ikhtibārī. In accordance with KMA No. 374 of 2022, the evaluation is conducted continuously by assessing cognitive, affective, and psychomotor aspects. This research focuses on developing a customizable imla learning method within the KMI pesantren curriculum that can meet the diverse needs of students by using simple yet effective teaching methods.